Dong Thap university journal of science: Natural sciences issue (Dong Thap University, 2020)
Content: A new approach to zero duality gap of vector optimization problems using characterizing sets; Cones generated by semi-infinite systems and their application on optimization; Convergence of Mann iteration process to a fixed point of - nonexpansive mapping in space;...